Building Literacy Through Reading and Storytelling Movements at Sinar Jaya Indonesia Orphanage - Winda Sri Astuti Doloksaribu; Maisara Batubara; Rahmat Alamsyah Harahap; Jarunjung Hutagaol; Mangasi Butarbutar; Lidya Natali Pasaribu; Mohd. Nawi Purba; Lina (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2026)
The current rapid development of technology allows literacy to be connected with technological, informational, and scientific literacy. A person's ability to read and write is the most fundamental aspect of developing broader literacy skills. The Indonesian population, according to the Central Statistics Agency, has only 10% interest in reading. This research uses a qualitative approach. The PKM activities were conducted using the Training and Mentoring method, where children were invited to read using the interactive storytelling method and the visual education method thru bilingual media using an English-Indonesian picture dictionary, which involved the use of interactive and colorful visual media. The result of the community service was that the activities were met with enthusiasm from both the foundation's chairman and the orphanage children. The storytelling method effectively alleviated the children's boredom with regular textbooks, fostering their curiosity and engaging them in interactive Q&A sessions during the story. This demonstrates that this method has proven to change the perception that reading is an exciting and enjoyable activity. With the distribution of colorful bilingual picture dictionaries, children are given an easier way to memorize everyday vocabulary, starting from body parts and objects around the house, thereby enriching their English vocabulary.